EMPOWERING SELF-RELIANCE FOR FOOD SECURITY WITH AISYIYAH SIDOARJO IN LIMITED LAND UTILIZATION - Abror, M; Eviyanti, Ade; Miftahurrohmat, A (Journal of Social Comunity Services, 2025)
Objective: This study aims to enhance food security by empowering the members of Pimpinan Daerah Aisyiyah (PDA) Sidoarjo through the utilization of narrow land for sustainable agriculture. Many Aisyiyah members possess home yards or small plots of land that remain underutilized, necessitating an intervention to promote efficient land use practices. Method: The program involved a series of activities, including socialization, training, and mentoring on various urban farming techniques such as polybag cultivation, hydroponics, and verticulture. These approaches were introduced to facilitate knowledge transfer and ensure the proper cultivation of organic crops through hands-on learning. Results: The implementation of hydroponic and organic farming methods was successfully adopted by Aisyiyah members, leading to an increase in household-scale agricultural productivity. Participants were able to cultivate crops until harvest, demonstrating the effectiveness of the provided training. Moreover, they developed the capability to create planting media and produce liquid organic fertilizers independently, reinforcing sustainable agricultural practices. Novelty: This initiative integrates community-based empowerment with technological advancements in urban farming, specifically targeting women-led organizations in the context of food security. The combination of hydroponic cultivation, organic farming, and independent fertilizer production offers a replicable model for optimizing land use in urban and peri-urban settings.